2017
DOI: 10.1007/s11130-017-0620-7
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Impact of Adherence to a Vegan Diet on Acid-Base Balance in Healthy Adults

Abstract: Acidogenic diets, commonly measured by the potential renal acid load (PRAL), have been linked with metabolic diseases including insulin resistance, hepatic dysfunction, and cardiometabolic risk. Vegan diets are linked to low dietary acid loads, but the degree of adherence to a vegan diet to demonstrate this benefit is unknown. This study compared the change in PRAL and urine pH of omnivores who followed a vegan diet for either 2, 3, or 7 days over one week. Healthy adults were recruited from a campus populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 23 publications
5
30
0
1
Order By: Relevance
“…An intervention study conducted in American adults showed that individuals would be able to lower their PRAL score by 13 units when following a vegan diet for two to three days a week, while a reduction of almost 30 units was seen in individuals following the vegan diet every day in a week [ 25 ]. If we examine our data from the DCH cohort, we find that a reduction of 30 units would be sufficient to move an individual from Q4 to Q1.…”
Section: Discussionmentioning
confidence: 99%
“…An intervention study conducted in American adults showed that individuals would be able to lower their PRAL score by 13 units when following a vegan diet for two to three days a week, while a reduction of almost 30 units was seen in individuals following the vegan diet every day in a week [ 25 ]. If we examine our data from the DCH cohort, we find that a reduction of 30 units would be sufficient to move an individual from Q4 to Q1.…”
Section: Discussionmentioning
confidence: 99%
“…Meat and meat products in particular are abundant in sulfur-containing amino acids (methionine, cysteine and homocysteine) [ 9 ]. Their oxidation generates sulfate, a non-metabolizable anion constituting a major determinant of the daily acid load [ 9 , 10 ]. The content of methionine and cysteine is 2- to 5-fold higher in eggs and meat than in certain grains and legumes [ 9 ], which, in turn, are considered alkalinizing foods.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetables and fruits are abundant in potassium salts of metabolizable organic anions (mainly malate and citrate), which undergo combustion in the body to yield bicarbonate and consume hydrogen ions when metabolized, thus having an alkalinizing effect [ 9 , 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We appreciate the critique of our paper (Ciuris et al [1]) by Genoni et al [2]. Our research group has a track record of investigating the benefits of vegetarian nutrition, such as demonstrating that vegetarian diets promote healthful mood states [3,4] and improve acid-base balance [5], along with, developing an evidence-based vegetarian food guide [6]. However, our research also suggests that lower protein intakes among vegetarians may pose challenges for some health outcomes; specifically we have linked lower protein intakes in vegetarians to lower bone mineral density [7] and strength [8].…”
mentioning
confidence: 93%